Pulmonary inflammatory myofibroblastic tumor in children - Wawszczak, Maria; Kraj, Grażyna; Lange, Joanna; Langfort, Renata (Pediatria Polska - Polish Journal of Paediatrics, 2023)
Inflammatory myofibroblastic tumor (IMT) is a rare neoplasm characterized by mesenchymal spindle cell proliferation with a marked inflammatory infiltrate component. Although the exact etiopathology of pulmonary IMT is still not clear, gene fusions involving anaplastic lymphoma kinase (ALK) or ROS proto-oncogene 1, receptor tyrosine kinase (ROS1), neurotrophic tyrosine receptor kinase (NTRK), platelet-derived growth factor receptor (PDGFR) and rearranged during transfection (RET) have been recently detected in immunohistochemical assessment of this lesion. Due to its nonspecific clinical or radiological presentation, the diagnosis of IMT primarily depends on histopathological findings. Surgery remains the mainstay of treatment and provides the best chance to limit recurrence. In unresectable lesions or multifocal/metastatic disease, treatment with chemotherapy or ALK, ROS1, RET and NTRK inhibitors is recommended. The prognosis in children with IMT is generally perceived as favorable, although local invasion and metastasis have been reported.